2013
DOI: 10.1007/s00403-013-1324-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of AQP3 in UVA-induced NHSFs apoptosis via Bcl2 up-regulation

Abstract: Aquaporin-3 (AQP3), a water/glycerol-transporting protein that facilitates water, urea, and glycerol transport, can inhibit arsenite-induced apoptosis by up-regulating Bcl-2. However, whether it has a protective role in ultraviolet A (UVA)-induced apoptosis in normal human skin fibroblasts is not known. In this study, we demonstrate that mild UVA treatment fails to induce oxidative cell stress and apoptosis in normal human skin fibroblasts (NHSFs) overexpressing AQP3. After severe UVA irradiation, there was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…As UVA irradiation increases, oxidative stress levels and apoptosis increase, which further decreases AQP3 expression. In contrast, in AQP3-overexpressing primary normal human skin fibroblasts that have been exposed to severe UVA irradiation, apoptosis and oxidative stress were strongly decreased (Xie et al 2013). Recently resveratrol, a natural polyphenol was found to downregulate AQP3 expression in human keratinocytes (Wu et al 2014).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As UVA irradiation increases, oxidative stress levels and apoptosis increase, which further decreases AQP3 expression. In contrast, in AQP3-overexpressing primary normal human skin fibroblasts that have been exposed to severe UVA irradiation, apoptosis and oxidative stress were strongly decreased (Xie et al 2013). Recently resveratrol, a natural polyphenol was found to downregulate AQP3 expression in human keratinocytes (Wu et al 2014).…”
Section: Discussionmentioning
confidence: 94%
“…EPA attenuates UVB-induced cell death and downregulation of cell proliferation Recent report has indicated that overexpression of AQP3 protected against high-dose UVA-induced oxidative stress and apoptosis in human skin fibroblasts (Xie et al 2013). Therefore, we have investigated the protective effects of EPA against UVB-induced cytotoxicity.…”
Section: Epa Induces Erk Activation In Cultured Human Keratinocytesmentioning
confidence: 98%
“…We previously demonstrated that upregulation of AQP3 expression contributes to the proliferative activity of GC cells 3. AQP3 expression has also been implicated in the regulation of cell apoptosis 35,36. But the association between AQP3 expression and cell apoptosis in GC has not been elucidated in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al35 demonstrated that AQP3 contributes to the inhibition of cell apoptosis in normal human skin fibroblasts by upregulating the expression level of Bcl-2, an anti-apoptosis protein. Hou et al17 also reported that AQP3 knockdown clearly induces cell apoptosis in non-small cell lung cancer but failed to clarify the detailed pathogenic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, altered AQP3 expression and production have also been linked to several skin diseases such as eczema [9, 38], psoriasis, non-melanoma skin cancers [23, 31, 44, 52] and vitiligo [29]. Recently, AQP3 has also been shown to play a protective role in UV-induced apoptosis in fibroblasts [54] and has also been suggested to be a participating factor in skin aging [45]. Thus, AQP3 is a key player in the skin and identifying compounds that modulate its activity could yield new therapeutic actives for drug development and skin care.…”
Section: Introductionmentioning
confidence: 99%